2009
DOI: 10.1016/j.molcel.2009.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Formation of an Active Signaling Complex between Rac and Phospholipase C Gamma 2

Abstract: Rho family GTPases are important cellular switches and control a number of physiological functions. Understanding the molecular basis of interaction of these GTPases with their effectors is crucial in understanding their functions in the cell. Here we present the crystal structure of the complex of Rac2 bound to the split pleckstrin homology (spPH) domain of phospholipase C-gamma(2) (PLCgamma(2)). Based on this structure, we illustrate distinct requirements for PLCgamma(2) activation by Rac and EGF and generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 40 publications
4
61
0
Order By: Relevance
“…PLCγ mutations in immune disorders Table 2. PLCγ mutations in cancer been discovered that PLCγ2 is also activated by the small GTPase Rac [40,41]. by a phosphorylation independent mechanism (dotted arrow).…”
Section: Resultsmentioning
confidence: 99%
“…PLCγ mutations in immune disorders Table 2. PLCγ mutations in cancer been discovered that PLCγ2 is also activated by the small GTPase Rac [40,41]. by a phosphorylation independent mechanism (dotted arrow).…”
Section: Resultsmentioning
confidence: 99%
“…These states were initially described for H-Ras as having low versus high affinity, respectively, toward Ras effectors (39). (ii) Stabilization of the Phe-897 side chain was in one of the two conformational states observed in the crystal structures of free spPH (25). Replacement of Phe-897 in human PLC␥ 2 spPH by the corresponding human PLC␥ 1 residue glutamine is expected to reduce the hydrophobic momentum of the Rac2 binding pocket on PLC␥ 2 spPH and, possibly, interfere with the reorientation of the Leu-67 side chain upon complex formation (Fig.…”
Section: Point Mutation F897q Renders the Dt40 Cell Plc␥ 2 Orthologuementioning
confidence: 97%
“…Mutational and structural analyses have shown that the stimulation of human PLC␥ 2 by activated Rac GTPases is due to an interaction of the Rac switch I and II regions with specific residues in the C-terminal half of the PLC␥ 2 spPH domain (24,25). Fig.…”
Section: Point Mutation F897q Renders the Dt40 Cell Plc␥ 2 Orthologuementioning
confidence: 99%
See 2 more Smart Citations